Trust and Quality of Growth: A Note - Simplice A. Asongu; Rangan Gupta (African Governance and Development Institute (AGDI), 2015)
The transition from Millennium Development Goals (MDGs) to Sustainable Development Goals (SDGs) has substantially shifted the policy debate from growth to inclusive growth. In this short note, we revisit the trust-growth nexus by exploiting a dataset on quality of growth (QG), recently made available to the scientific community. The empirical evidence is based on interactive contemporary and non-contemporary quantile regressions. Inequality and human development modifying variables are used as additional controls. The findings broadly support the positive role of trust in QG. In addition, relatively high thresholds of inequality are needed to change this positive trust-QG nexus in some distributions.
Keywords: A13; I30; O40; Z13; 330; Trust; Inclusive Growth; Conditional Effects